2021
DOI: 10.21037/jgo-21-491
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and postoperative blood glucose value help predict posthepatectomy liver failure in patients with hepatocellular carcinoma

Abstract: Background: Many complications after hepatectomy can lead to perioperative death, among which posthepatectomy liver failure (PHLF) is the leading one. Existing studies suggest that one of the most important risk factors for PHLF is cirrhosis. Hepatitis B virus (HBV) infection is an important factor in the occurrence of cirrhosis, and the exact relationship between HBV infection and PHLF is not obvious. Diabetes mellitus and postoperative blood glucose are closely associated with liver regeneration, but its exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Although it is not the most identified patient related risk factor, the presence of diabetes has been proven to be significantly associated with a risk of PHLF. 30,31 As demonstrated in several previous studies, 6,29,32 volume does not necessarily correlate with liver function, usually underestimating it. This can be explained by several aspects.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Although it is not the most identified patient related risk factor, the presence of diabetes has been proven to be significantly associated with a risk of PHLF. 30,31 As demonstrated in several previous studies, 6,29,32 volume does not necessarily correlate with liver function, usually underestimating it. This can be explained by several aspects.…”
Section: Discussionmentioning
confidence: 75%
“…Concerning patient related data, both groups were equivalent except regarding diabetes. Although it is not the most identified patient related risk factor, the presence of diabetes has been proven to be significantly associated with a risk of PHLF 30,31 …”
Section: Discussionmentioning
confidence: 99%
“…Recently, LLR is gradually replacing traditional open hepatectomy, and has become the mainstream surgical method for HCC due to its advantages of minimal invasiveness ( 15 , 16 ). In several OLR study series, preoperative T2DM has been reported to be associated with an increased risk of postoperative morbidities ( 17 , 33 ) and have a direct negative impact on survival of HCC ( 34 36 ). While LLR is gaining a rapid popularity among liver surgeons, however, little is known regarding the downstream effect of T2DM after such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…Two propensity score matching (PSM) studies showed that LLR is as safe and effective as open liver resection (OLR) for HCC patients ( 15 , 16 ). In previous OLR series, pre-existing T2DM was reported to have direct negative impact on short-term postoperative outcomes and long-term prognosis ( 17 , 18 ). Wang et al ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…LR is a synchronized multistep process consisting of initiation (2 to 6 h), proliferation (12 to 72 h) and termination (120 to 168 h) [ 8 , 9 ]. However, the regeneration potential of liver is often impaired by pathological factors, such as liver failure and liver cirrhosis [ 10 , 11 ], thus it is worth emphasizing the necessity of finding novel channels to improve liver’s regenerative potential.…”
Section: Introductionmentioning
confidence: 99%